Vitamin D and Vitamin D Analogs as Adjuncts to Field Therapy Treatments for Actinic Keratoses: Current Research and Future Approaches. (19th June 2021) - Sattouf, Zafer; Repas, Steven J.; Travers, Jeffrey B.; Rohan, Craig A.
Abstract : Actinic keratoses (AK), also known as solar keratoses, are precancerous hyperkeratotic papules caused by long-term exposure to ultraviolet radiation. Management of AK prior to progression to cutaneous malignancy represents an important window of intervention. This is important on a population level, given the high incidence, morbidity, financial costs, and the low but measurable risk of mortality from cutaneous neoplasia. Treatments for AK have been refined for many years with significant progress over the past decade. Those recent advancements lead to questions about current treatment paradigms and the role of harnessing the immune system in field therapies. Recent studies suggest a key interplay between vitamin D and cancer immunity; in particular, the systemic and/or topical vitamin D analogs can augment field therapies used for severe actinic damage. In this review, we will examine the literature supporting the use of vitamin D-directed therapies to improve field therapy approaches. An enhanced understanding of these recent concepts with a focus on mechanisms is important in the optimized management of AK. These mechanisms will be critical in guiding whether selected populations, including those with immunosuppression, heritable cancer syndromes, and other risk factors for skin cancer, can benefit from these new concepts with vitamin D analogs and whether the approaches will be as effective in these populations as in immunocompetent patients.